Draft Genome Sequence of Klebsiella pneumoniae OK8, a Multidrug-Resistant Mouse and Human Pathogen - Nagamalleswari, Easa (Genome Announc, 2017)
We report here the draft genome sequence of Klebsiella pneumoniae OK8, a multidrug-resistant strain which was isolated in 1976 from a human and is known to be a mouse pathogen.